Ontogenetic development of larval hybrid Malaysian mahseer [Barbonymus gonionotus (Bleeker 1850) ♀ × Tor tambroides (Bleeker 1854) ♂] - Ismail, Muhammad Azfar (2019)
Hybrid Malaysian mahseer, a crossbreed between male Malaysian red mahseer, Tor tambroides and female silver barb, Barbonymus gonionotus, was an effort to produce better tropical carp strains and help reduce the pressure on fisheries of endangered mahseers. The study was carried out to observe and describe the morpho-histological development of the hybrid Malaysian mahseer for the entire duration of its larval stage. Upon hatching, larvae were reared in the aquaria at a stocking density of 5-10 larvae l-1. The larvae were observed daily from 1 to 10 DAH (day after hatching) and at 2-dayintervals until the completion of the post-larval stage within 25 DAH by means of light and scanning electron microscope (SEM), and histology. Newly hatched larvae were transparent with closed mouth and anus, and a simple tubal gut formation. The hybrid larvae commenced exogenous feeding by 3 DAH with the mouth opening of 111.01 ± 5.91 μm Ø and 173.11 ± 10.98 μm Ø at 45ο and 90ο, respectively. The taste buds and neuromasts were the first to function in early larval stage, followed by eyes, inner ear and olfactory as the fish grew. Unlike the parents, the hybrid mahseer was barbel-less. It seemed that the abundance of taste buds at the premaxilla compensated the absence of barbels for detecting food organisms in the earlier feeding stage. At 4 DAH, the reserve yolk sac was completely reabsorbed by the larvae while the mouth was terminal at 6 DAH. A true functional stomach was observed by 7 DAH with the relative gut index (RGI) of 10.7 ± 0.06. The findings indicated that the hybrid larvae could be gradually or totally weaned to an artificial diet of a suitable particle size at this stage. Complete tissue layers (mucosa, submucosa, muscularis and serosa) were visible in the larval gut by 18- 21 DAH indicating the end of the larval stage. The post larval stage of the hybrid Malaysian mahseer was short and completed by 23-25 DAH when the scales fully covered its body.